(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper investigates the relationship between internet connectivity and productivity within the framework of top-level management in management institutes. The study aims to explore the perceptions and opinions of top-level management professionals regarding the impact of reliable internet connectivity on their work practices, teaching methodologies, administrative tasks, and overall institutional efficiency. A sample of 400 respondents from management institutes in Pune, India, participated in the study. The research design employed a cross-sectional survey approach, and data was collected using a structured questionnaire featuring Likert-scale items. The data were analyzed using descriptive statistics and hypothesis testing, including Pearson’s Correlation Coefficient. The findings highlight a positive relationship between internet connectivity and perceived productivity among respondents, revealing that enhanced connectivity contributes to efficient task execution.